A little thing called life ebook On loving elvis presley, bruce jenner, and songs in between. - Thompson, Linda (2016)
Award-winning songwriter Linda Thompson breaks her silence, sharing the extraordinary story of her life, career, and epic romances with two of the most celebrated, yet enigmatic, modern American superstars—Elvis Presley and Bruce Jenner For the last forty years, award-winning songwriter Linda Thompson has quietly led one of the most remarkable lives in show business. The longtime live-in love of Elvis Presley, Linda first emerged into the limelight during the 1970s when the former beauty pageant queen caught the eye of the King. Their chance late-night encounter at a movie theater was the stuff of legend, and it marked the beginning of a whirlwind that would stretch across decades, leading to a marriage with Bruce Jenner, motherhood, and more drama than she ever could have imagined. Now, for the first time, Linda opens up about it all, telling the full story of her life, loves, and everything in between. From her humble beginnings in Memphis to her nearly five-year relationship with Elvis, she offers an intimate window into their life together, describing how their Southern roots fueled and sustained Graceland's greatest romance. Going inside their wild stories and tender moments, she paints a portrait of life with the King, as raucous as it is refreshing. But despite the joy they shared, life with Elvis also had darkness, and her account also presents an unsparing look at Elvis's twin demons—drug abuse and infidelity—forces he battled throughout their time together that would eventually end their relationship just eight months before his untimely death. It was in the difficult aftermath of Elvis's death that Linda found what she believed was her true home: the arms of Olympic gold medal—winner Bruce Jenner. Detailing her marriage to Bruce, Linda reveals the seemingly perfect life that they built with their two young sons—Brandon and Brody—before Bruce changed everything with a secret he'd been carrying his entire life, a secret that Linda herself kept for nearly thirty years, a secret that Bruce's transition to Caitlyn Jenner has finally laid bare for the world. Providing a candid look inside one of the most challenging moments of her life, Linda uncovers the struggles she went through as a woman and a mother, coming to terms with the reality of Bruce's identity and resolving to embrace him completely no matter what, even as it meant they could no longer be together. And yet, despite her marriage unraveling, her search for love was not over, eventually leading her to the legendary music producer and musician David Foster—a relationship that lasted for nineteen tumultuous years, resulting in a bond that spurred her songwriting career to new heights but also tested her like never before. Filled with compelling and poignant stories and sixteen pages of photographs, A Little Thing Called Life lovingly recounts Linda's incredible journey through the years, bringing unparalleled insight into three legendary figures.